Nature and Classification of Tropical Climates with Special Reference to India - Subrahmanyam, V. P. (Indian Forester, 1969)
The paper deals with a critical account of tbe application of the Thornthwaite scheme for the classification of climates of the Indian region. Starting with the physical origin of climates, discussion is made of the need for and purpose of climatic classifications. Brief reference is made to the familiar Koppen scheme of classification of tropical climates and its uniqueness in recognizing plants as climatic indicators. Considering next the importance of moisture and heat factors in ecoclimatic studies, it is shown how the scheme put forth by Thornthwaite, based On his own concept of potential evapotranspiration, meets the full ecological requirements of climatic classification, Delineation of the tropical climates of India is then dealt with according to Thornthwaite's classification, with special reference to the moisture and thermal regimes. Emphasis is laid on the summer concentration of thermal efficiency in relation to the growth and development of natural vegetation. The role and evaluation of water balance in climatic studies are then described in all their various aspects and climatic water balance charts are presented for typical Indian stations belonging to the six major climatic types from Perhumid to Arid. The paper concludes by reference to the use of aridity indices in the study of drought climatology, as already reported in the published work by the author and his co-workers. It is reiterated that the water balance approach be thoroughly investigated and developed in view of its rational and universal nature, for an objective assessment of the water potentialities or different climatic regions in hydrological and agricultural planning.